Biomechanical strength of glass ionomer cement in incudostapedial rebridging - Server, E. A.; Alkan, Z.; Yigit, O.; Acioglu, E.; Bekem, A.; Unal, A.; Akkin, S. M. (CAMBRIDGE UNIV PRESS, 2015)
Objective: To study the biomechanical properties of glass ionomer cement used for incudostapedial rebridging. Methods: Two groups were established based on the size of the gap between the incus and stapes (1.0mm in group 1 and 2.0mm in group 2). Glass ionomer cement was applied to the gaps, and compression tests were performed. Maximum force was measured at the fracture point, and was divided by the cross-sectional area to obtain the maximum compressive strength. Results: No significant difference was found in the maximum force for the two groups (p=0.312). The glass ionomer cement diameter was significantly higher in group 2 than in group 1 (p=0.006). The maximum compressive strength was significantly higher in group 1 than in group 2 (p=0.042). Conclusion: The fragility of bone cement used in this study was 25.5 per cent higher for a 2 mm gap than for a 1 mm gap. We speculate that the use of bone cement may be safer for the repair of smaller incudostapedial defects.
Keywords: Bone Cements; Incus; Stapes; HYDROXYAPATITE BONE-CEMENT; OSSICULAR RECONSTRUCTION; MIDDLE-EAR; OSSICULOPLASTY; CHAIN; JOINT; Otorhinolaryngology